Studies on the Application of Leaf Isolates of Lactic Acid Bacteria as PGPR - Anisha Jadhav,; Dr. P.S. Abhyankar,; Dr. R.B. Patwardhan, (The Bioscan, 2025)
The rhizosphere of a plant contains microorganisms that can be called plant growth-promoting rhizobacteria (PGPR), which play a crucial role in promoting plant growth and development. The beneficial effects of these bacteria on plant growth can be direct or indirect. The benefits provided by these bacteria can include increased nutrient availability, phytohormone production, and protection against several phytopathogens. PGPR has become an important strategy in sustainable agriculture due to the possibility of reducing synthetic fertilizers and pesticides, promoting plant growth, and enhancing soil quality. Lactic Acid Bacteria (LAB) are ubiquitous, Gram-positive, catalase-negative, and facultative aerophilic microorganisms. They are commonly found in a wide range of environments including food-rich environments, decaying plants, milk products, the human gut, vaginal flora, and on the skin of various living organisms. Their applications are seen in food fermentation, food preservation, the pharmaceutical industry, and dietary supplements. In addition, their presence in the rhizosphere expands their application as PGPR. The LAB isolated from soil and plant parts shows significant production of phytohormones like indole acetic acid, gibberellic acid, etc. They also show antimicrobial activity against phytopathogens. Their ability to fix nitrogen, iron chelation, phosphate solubilization, and ammonia production makes them the PGPR. In this paper, the PGPR characteristics of LAB and other reported PGPR are compared.